2012
DOI: 10.4315/0362-028x.jfp-11-233
|View full text |Cite
|
Sign up to set email alerts
|

Survival In Vitro and Virulence of Trypanosoma cruzi in Açaí Pulp in Experimental Acute Chagas Disease

Abstract: Chagas disease is a parasitic infection with high socioeconomic impact throughout Latin America. Although this severe, incurable disease can be transmitted by several routes, oral transmission is currently the most important route in the Amazon Basin. Açaí pulp has nutritional properties and is popular throughout Brazil and abroad. However, this pulp has been associated with microepidemics of acute Chagas disease (ACD) in northern Brazil, where açaí fruit is the main food supplement. In this study, we examined… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(14 citation statements)
references
References 10 publications
1
11
0
2
Order By: Relevance
“…Some of the researches supported phytase enzyme and agree with the results of our research Barbosa et al, (2012) found that the addition of phytase, amylase, xylanase, and protease to diets with reducing in energy, calcium, and phosphorus content, give similar result feed intake and weight gain compared with a diet had adequate nutrient levels. Stefanello et al, (2015) showed that the diets supplemented with phytase and with xylanase led to improve growth performance of broiler.…”
Section: Resultssupporting
confidence: 88%
“…Some of the researches supported phytase enzyme and agree with the results of our research Barbosa et al, (2012) found that the addition of phytase, amylase, xylanase, and protease to diets with reducing in energy, calcium, and phosphorus content, give similar result feed intake and weight gain compared with a diet had adequate nutrient levels. Stefanello et al, (2015) showed that the diets supplemented with phytase and with xylanase led to improve growth performance of broiler.…”
Section: Resultssupporting
confidence: 88%
“…This simulation was repeated 15 times, and only once did the professionals identify the insect. It is noteworthy that this transmission can occur with the consumption of not only freshly made juice, but also frozen juice [34], [38]. These authors demonstrated that infective T. cruzi can survive in açaí pulp at room temperature for 48 h, at 4°C for 144 h and at −20°C for 26 h.…”
Section: Discussionmentioning
confidence: 95%
“…The Chichiriviche outbreak, however, has potential sources both in and outside the immediate area. As found in Chagas disease outbreaks linked to açaí palm fruit in Brazil ( 12 ), the T. cruzi parasite can survive for several days in some foodstuffs ( 13 ). Also, triatomines can survive for months in harvested crops; thus, multiple hygiene interventions are potentially necessary along the food production line ( 14 ).…”
Section: Discussionmentioning
confidence: 99%